The Adaptation Community Based Indigenous Knowledge Post Earthquake Disaster Recovery in Solok Selatan Indonesia - Diana, Deni; Sukardi, L. (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Abstract Research's purposed to gain data, collect, process, and analyze and describe adaptation community based indigenous knowledge in recovery disaster post- disaster quake South Solok. Method research that used is method qualitative being focused at excavation information about adaptation community that composed of adaptation social, adaptation economy, and adaptation physical / residential. Research's carried in Sangir, district South Solok. In research's included 10 people as the informant, the prescribed with way snowballed and accompanied by readiness they engage in researches. Data that gathered use engineering observation, interview, and documented. Data analysis in research done with use engineering reduction data, interpretation data and retrieval conclusion. Result research show that: 1). Adaptation indigenous knowledge shape building community after occurring quake in district South Solok that is society back use indigenous knowledge that is trying to established building with use material-bachelor of arts) than quality well and of course with material wood with shape building stilt house, 2). Adaptation indigenous knowledge cooperate-mutual in social life after occurring quake in district South Solok that is worked-mutual inter protect one equal other in face disaster, 3). Adaptation indigenous knowledge community in thing activity religion after occurring quake in district South Solok that does recitation for more bring closer self to the creator, 4). Adaptation wisdom local in thing shape economy community after occurring quake in district South Solok that seeks to not working forest prohibition for economic activity because worried about happening of imbalance balance nature, 5). Adaptation indigenous knowledge community against knowledge about quake after occurring quake in district South Solok that is trying to understand what action that must be done when occurring disaster and should keep control oneself, 6). Adaptation indigenous knowledge community against forest management about quake after occur quake in district South Solok that is forest management post-disaster try so that forest such reduced for plant oil palm so that water supply people not decreased and not occur avalanche.